PENGARUH PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS JAGUNG MANIS (Zea mays saccharata Sturt.) - Nurul Husnina; Syafruddin Syafruddin; Erida Nurahmi (Universitas Teuku Umar, 2018)
This research aims to knows the influence the types of organic fertilizer towards the growth and yield some varieties of sweet corn, as well as the interaction between the types of organic fertilizer with varieties of sweet corn. This research was carried out in April to July 2016 at the Experimental Farm Agriculture Faculty of Syiah Kuala University Banda Aceh. Research design used was Random Design Group Factorial pattern of 4 x 3 with 3 replicates. Factors that researched the types of organic fertilizer consisting of 4 levels, namely: without the use of fertilizer, manure, compost and mycorrhiza. The factor varieties consisting of 3 levels, namely varieties of Bonanza, varieties of Jambore and varieties of Sweet Boy. The results showed that use of mycorrhiza growth and yield of sweet corn plants are better, whereas varieties of Sweet Boy is a better variety. The next better interactions present in these types of mycorrhiza with use of organic fertilizer varieties of Sweet Boy on a high percentage of the crop parameters age 30 days after planting (DAP), number of leaves the age of 15, 30, and 45 (DAP) and potential outcomes. The real effect on plant height parameters age 45 HST, the length of the cob without bractea, the heavy cob with bractea each plants, and infection of mycorrhiza on plant roots.Keywords : Compost, manure, mycorrhiza, organic fertilizer, sweet corn, varieties